Mapeamento e análise de áreas de destinação de resíduos da construção civil em Francisco Beltrão - PR - Biluca, Juliana (2017)
The growing urbanization of cities, with the construction of homes and workplaces, has generated negative environmental impacts due to the inadequate disposal of construction waste (CW), resulting in risks for the environment and the population. According to the legislation, the proper destination of construction waste is dependent on the class in which they fall. For Class A waste, those with the possibility of reuse or recycling in the building itself, the appropriate destination is the recycling plants or landfills where they are reserved for future uses. The installation of these developments must follow laws and regulations to minimize the negative impact. Therefore, the present study aimed to identify and characterize the areas of inadequate disposal of CW in the in the municipality of Francisco Beltrão - PR, as well as to map suitable sites for the installation of a landfill associated to a construction waste recycling plant. The areas of inadequate disposal were characterized in terms of size, situation, type of waste, land use and occupation, slope, distance to water bodies and highways. These data were normalized with fuzzy logic and had weights of importance established with the Analytic Hierarchy Process (AHP), with which we can perform the weighted linear combination of different criteria and the generation of two indices, environmental degradation and material utilization. In order to map the appropriate areas to the CW, the soil type, slope and land use and occupation were analyzed, as well as distances to population centers, health and education institutions, roads and highways and hydrography. The data were also normalized and had weights of importance established so that they could be combined linearly to obtain the suitability map. The program used for data manipulation was ArcGis 10.0. The environmental degradation index of the disposal areas identified 30.42% of medium, 26.09% of high and 26.09% of low potential of degradation, the rest have intermediate values. On the other hand, the utilization index identified that 56.25% of the areas are high, 25% are low and 18.75% have a medium potential for use. The suitability map identified approximately 5 km² of apt areas, ranging from low, medium and high suitability.